TINJAUAN YURIDIS PERJANJIAN PERDAMAIAN PADA PROSES PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - Leonard, Tommy; Irianda Panjaitan, Yolanda C. (IBLAM LAW REVIEW, 2023)
Peace agreements are crucial to PKPU's goal of helping creditors restructure their debts. This research addresses how to arrange the peace agreement as a debt restructuring step in the Postponement of Debt Payment Obligations (PKPU), how it is used in the Suspension of Debt Payment Obligations process in Decision Number 90/Pdt.PKPU/2020/PN Niaga.Jkt.Pst, and how the ratification of the peace agreement is related to the absence of a Compensation for Services for the Management Team agreement. This thesis uses normative legal descriptive analysis—literature-based data collecting. Data analysis was qualitative. Peace agreements as debt restructuring in PKPU are regulated under Articles 265-294 of the Civil Code in Chapter III of the PKPU UUK. The debt restructuring and receivables collection allowed the Debtor to enhance his business conditions under the peace agreement. The judge granted the peace agreement in the PKPU process in Decision Number 90/Pdt.PKPU/ 2020/Pn.Jkt.Pst based on legal considerations based on Article 281 paragraph (1) letters a and b UUK PKPU. There is no reason to reject the debtor's peace plan despite criticism from one creditor. The peace agreement was ratified without a Management Team compensation agreement in the PKPU procedure in Decision Number 90/Pdt. The judge, PKPU/2020/Pn.Jkt.Pst, stated that the Management Team's pay could be established separately after the Homologation Decision. Therefore, the Ratification of the Peace should be accepted.